A Study to Examine the Relationship between Mathematical Creativity and Mathematical Problem-solving Performance - Tyagi, Tarun Kumar (JOURNAL OF INDIAN EDUCATION, 2015)
The present study aimed to investigate whether a relationship exists between the mathematical creativity and mathematical problems solving performance. As bi product of the main study the sex and cultural differences were also examined in the study. In addition, whether the both variable differ with respect to gender and locality. Data were collected from four hundred eighty participants (201 male and 279 female) of eighth grade standard selected through random cluster technique from eight intermediate and high schools located in Varanasi region, India. Data were analysed by Pearson moment correlations, t-test and simple regression analysis. The results showed positive and significant relationship between mathematical problem solving performance and mathematical creativity. Male students were found to be significantly higher on both mathematical problem solving performance and mathematical creativity than their counterparts. Mathematical problem-solving performance significantly contributed in the prediction of mathematical creativity.